Disintegration reversed: Brexit and the cohesiveness of the EU27. Issue 3 (3rd July 2021) - Chopin, Thierry; Lequesne, Christian
ABSTRACT: This contribution analyses the political impact of Brexit on the EU27. The main argument is that Brexit is not just about disintegration. The UK policy proposals on Brexit have reinforced among the governments, public opinions and even Eurosceptic parties of the EU27 the cohesiveness in favour of the preservation of European integration. The article is divided into four parts. First, it presents a critical review of the theoretical literature on EU disintegration and defines the concept of cohesiveness. In the second section, it analyses why the EU27 member states remained cohesive during the Brexit negotiation talks on major policy issues such as the Single Market, free movement of persons and budgetary contribution. In the third section, the article explains why Brexit did not succeed to convince the public opinions of the EU27 that leaving the EU was a relevant issue. In the fourth section, it analyses the reasons why Eurosceptic parties (especially right wing ones) within the EU27 started using Brexit as a strategic argument against EU integration but quickly abandoned it in favour of the request that EU must be changed from inside.